Utilização de garrafas PET pós-consumo como revestimento anticorrosivo em aços - Elisângela Aparecida da Silva (2019)
The increasing use of post-consumer PET packaging (PET-PC) has the consequence of increasing the volume of solid waste. The reuse of polymeric material is an alternative for mitigating environmental damages. This work aims the development of PET-PC coating for steel application. The PET-PC bottles were submitted to the comminution process and the powder generated was deposited mechanically on the steel surface. The PET layer showed a good adhesion on the substrate when compared with the traditional organic coatings. In addition, scanning electron microscopy (SEM) analysis showed that the PET layer was uniform, homogeneous and free of cracks or defects. The Fourier-transform infrared spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) proved that the PET properties were not affected by the deposition process. The corrosion protection of PET-PC coatings was evaluated by the accelerated corrosion test in salt spray and by the technique of electrochemical impedance spectroscopy (EIS). After 480 hours of exposure to the salt spray chamber, the PETPC coating showed no bubbles, blistering, or displacement. The EIS showed that the PET coating has a capacitive effect and its electrochemical behavior was not affected as the exposure time increased, resulting in an impedance modulus value of 1010 ohm cm², after 576 h of immersion in an aqueous solution of NaCl 3.0 wt.%. The PET-PC organic coating is promising; however, zinc particles were added to the polymer coating aiming at the use of a primer. Several concentrations of zinc were tested but the concentration of 60 wt.% zinc in PET-PC showed a better cathodic protection effect.